Hubungan Pola Makan dan Aktifitas Fisik Terhadap Kejadian Diabetes Melitus di Poliklinik Penyakit Dalam RSUD dr. Rasidin Padang: The Relationship between Diet and Physical Activity to the Incidence of Diabetes Mellitus in the Internal Medicine Polyclinic at RSUD dr. Rasidin Padang - Putri Dafriani (Fakultas Keperawatan Universitas Andalas, 2017)
The aim of research to determine the relationship of diet and physical activity with the diabetes mellitus in the Internal Disease Polyclinic dr Rasidin Padang. This type of research is analytic with cross sectional design which was held on August 23 to 29 year 2016. The population of the patients who visit the Internal Disease Polyclinic dr Rasidin Padang Hospital. Number of samples 93 with a sampling technique accidental sampling. Data processing through stages of editing, coding, entry, cleaning and tabulating. The data collection is done by collecting primary and secondary data. The data analysis univariate using descriptive statistic and bivariate using Chi Square test with confidence level of 95% α = 0.05. The survey results revealed less than half the respondents is 39 respondents (41,9%) had DM Incidence, more than half of respondents is 52 respondents (55.9%) had not good diet, 49 respondents (52,7%) had light physical activity. Statistical test results are known there are relationship between diet and physical activity and the incidence of DM. It can be concluded that there are relationship between diet and physical activity and the incidence of DM. Expected to need to adjust your diet and doing regular physical activity, especially for people who have a family history of diabetes mellitus.